Supporting the Installation of Comprehensive, Integrated, Three-Tiered Models of Prevention: Educator Perspectives - Oakes, Wendy Peia; Lane, Kathleen Lynne; Royer, David James; Buckman, Mark Matthew; Common, Eric Alan; Allen, Grant Edmund; Cantwell, Emily Dawn (Frontiers in Education, 2022)
We provide results from a district-wide survey of 253 certified educators to determine (a) the degree to which they reported implementing components of their school’s comprehensive, integrated, three-tiered (Ci3T) model of prevention in the current year and (b) the areas in which educators might benefit from continued professional learning. The purpose of this study was to develop a data informed professional learning plan to continue to support implementation at the conclusion of an Institute for Education Sciences (IES) -funded practitioner-researcher partnership grant. At least half of educators reported a high level of implementation for all Tier 1 features. Tier 2 and Tier 3 behavioral and social supports for students were reported as less fully implemented than academic interventions, yet still well-above the scale midpoint. For every component, elementary educators indicated statistically significantly higher levels of implementation relative to secondary educators. Over half of respondents indicated a high level of implementation of eight of 20 research-based practices and supports examined, with a statistically significant relation between ratings of currently implemented practices and the desire for support in four practices: small-group self-determination instruction, peer-mediated support strategies, check-in/check-out, and strategies for internalizing behaviors. In terms of preferred professional development avenues, educators rated in-district during-school workshops, courses for college credit (on-line), and brief “good practice” guides most favorably. We close with a discussion of implications, limitations, and future directions.